Association of patient tumour characteristics and 5-Year survival in women with breast cancer in Nigeria: A retrospective cohort study - Omolara Fatiregun; Nwamaka N Lasebikan; Emmanella Nwachukwu; Boluwatife Borisade; Jimoh Mutiu; Anthonia C Sowunmi; Nnodimele Atulomah (Babcock University Medical Journal, 2025)
Objective: The sociodemographic and biological profiles of breast cancer differ globally, especially in women of African descent. In Nigeria, limited studies explore the impact of these breast cancer-related factors on survival. This study evaluated the association between patients' tumour characteristics and survival in breast cancer patients in three regional tertiary cancer treatment centres across Nigeria.